Causes of mortality in Mute Swans Cygnus olor in Scotland 1995-1996 - Pennycott, T W (Wildfowl, 1999)
As part of a survey into the causes of mortality of wild birds, the carcases of 41 Mute Swans (Cygnus olor) were examined at S.A.C. Veterinary Science Division, Auchincruive, Ayr, Scotland, between January 1995 and December 1996. Birds were submitted for post mortem examination directly by members of the general public, by a local wildlife rehabilitation centre, or by other organisations with an interest in wild birds. Fourteen of the birds were received from one site during a five month period and were representative of a greater number of dead swans found on that site. The remaining 27 swans were received over the two years from several different sites as sporadic deaths. The most significant primary causes of death in the birds from the site with heavy mortality were lead poisoning and heavy parasitic burdens. In contrast, in birds submitted as apparent sporadic deaths, the commonest primary causes of death were trauma, starvation and aspergillosis.